Antenna Optimization and Design Based on Binary Coding - Geng, Junping; Jin, Ronghong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book investigates in detail the antenna optimization method with binary coding and their applications to antenna design. It introduces the binary coding principle and optimization method, the method of binary coding corresponding to geometry structure. In further, the designs by binary coding optimization method of following items are introduced, including multi-frequency antenna based on binary coding, low profile RFID tag antenna on metal, wideband directional antenna with low profile, mmWave antenna and UWB antenna. Additionally, improved hexagon unit to antenna optimization by binary coding method is given, and a new method of antenna design based on optimization of linear motion trajectory is presented in the end. This book proposes an automatic optimization method of meshed antenna based on binary coding, reduce the artificial a priori influence and find the best antenna. The book is intended for undergraduate and graduate students who are interested in antenna technology, researchers investigating high performance antenna, and antenna design engineers working on new antenna and the applications.
1 INTRODUCTION -- 2 BINARY CODING AND OPTIMIZATION METHOD -- 3 MULTI FREQUENCY ANTENNA DESIGN BASED ON BINARY -- 4 DESIGN LOW PROFILE RFID TAG ANTENNA ON METAL WITH BINARY CODING OPTIMIZATION METHOD -- 5 DESIGN WIDEBAND DIRECTIONAL ANTENNA WITH LOW PROFILE BY BINARY CODING OPTIMIZATION METHOD -- 6 DESIGN MM WAVE ANTENNA BY BINARY CODING OPTIMIZATION METHOD -- 7 DESIGN UWB ANTENNA BY BINARY CODING OPTIMIZATION METHOD -- 8 IMPROVED HEXAGON UNIT TO ANTENNA OPTIMIZATION BY BINARY CODING METHOD -- 9 ANTENNA DESIGN BASED ON OPTIMIZATION OF LINEAR MOTION TRAJECTORY.
Keywords: Telecommunication; Electronic circuits; Wireless communication systems; Mobile communication systems; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Wireless and Mobile Communication; Antennas (Electronics) -- Design; Binary-coded decimal system